PMMA-silica nanocomposite coating: Effective corrosion protection and biocompatibility for a Ti6Al4V alloy - Harb, Samarah Vargas [UNESP] (2020)
Ti6Al4V is the mostly applied metallic alloy for orthopedic and dental implants, however, its lack of osseointegration and poor long-term corrosion resistance often leads to a secondary surgical intervention, recovery delay and toxicity to the surrounding tissue. As a potential solution of these issues poly(methyl methacrylate)-silicon dioxide (PMMA-silica) coatings have been applied on a Ti6Al4V alloy to act simultaneously as an anticorrosive barrier and bioactive film. The nanocomposite, composed of PMMA covalently bonded to the silica phase through 3-(trimethoxysilyl)propyl methacrylate (MPTS), has been synthesized combining the sol-gel process with radical polymerization of methyl methacrylate. The 5 μm thick coatings deposited on Ti6Al4V have a smooth surface, are homogeneous, transparent, free of pores and cracks, and show a strong adhesion to the metallic substrate (11.6 MPa). Electrochemical impedance spectroscopy results proved an excellent anticorrosive performance of the coating, with an impedance modulus of 26 GΩ cm2 and long-term durability in simulated body fluid (SBF) solution. Moreover, after 21 days of immersion in SBF, the PMMA-silica coating presented apatite crystal deposits, which suggests in vivo bone bioactivity. This was confirmed by biological characterization showing enhanced osteoblast proliferation, explained by the increased surface free energy and protein adsorption. The obtained results suggest that PMMA-silica hybrids can act in a dual role as efficient anticorrosive and bioactive coating for Ti6Al4V alloys.